(untitled) (Cambridge, 2001)
This book provides a thorough and clear description of research findings in order to help clinicians make sound decisions concerning their clients' dangerousness. The book covers a broad spectrum of violent behaviour as well as crucial issues such as biological factors, domestic violence, and the influence of alcohol in violent behaviour. The book is divided into the following sections: Basic Issues in Violence Research, Mental Health Issues and Dangerousness, Family Issues and Dangerousness, Individual Characteristics and Dangerousness. It will serve as an important reference book that not only covers scientific literature but provides views on future directions for research and practice in this valuable field.
Keywords: Violence,Bạo lực xã hội; Psychological aspects,Tâm lý học